Group Cognitive-Behavioral Therapy for Reducing Anxiety in Middle-Aged Women - Rinaldi, Martaria Rizky; Musawwamah, Qisthi Al (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2024)
Middle-aged women are susceptible to experiencing anxiety, which, if left untreated, can lead to decreased productivity and hinder social interactions, ultimately impacting overall well-being. This study aimed to investigate the effectiveness of cognitive-behavioral group therapy in alleviating anxiety in middle-aged women. The research design employed a quasi-experimental approach with a one-group pre-test-post-test design and follow-up assessment. The participants included seven middle-aged women aged between 53 and 60 years (mean age = 56.71). They were selected based on screening results using the DASS42 anxiety scale, which indicated severe and very severe anxiety. Data collection consisted of pre-test, post-test, and follow-up assessments using the Beck Anxiety Inventory (BAI). Data were analyzed using the repeated measures ANOVA method. The results of the data analysis revealed an F-value of 120, p < .001, indicating significant differences between the pre-test, post-test, and follow-up assessments. Specifically, significant differences were found between pre-test and post-test (p < .001), pre-test and follow-up (p < .001), and post-test and follow-up (p < .001) results. These findings demonstrate the effectiveness of cognitive-behavioral group therapy in reducing anxiety among middle-aged women. Therefore, cognitive-behavioral group therapy emerges as a viable intervention for addressing anxiety in this demographic.